Activation of Transcription Factor EB Alleviates Tubular Epithelial Cell Injury via Restoring Lysosomal Homeostasis in Diabetic Nephropathy. (12th January 2022) - Wang, Shujun; Jing, Kaipeng; Wu, Hongluan; Li, Xiaoyu; Yang, Chen; Li, Tingting; Tang, Haoxuan; Zou, Ting; She, Yao; Liu, Hua-feng
Abstract : Disruption of lysosomal homeostasis contributes to the tubulopathy of diabetic nephropathy; however, its underlying mechanisms remain unclear. Herein, we report that decreased activity of transcription factor EB (TFEB) is responsible for the disturbed lysosome biogenesis and clearance in this pathological process. This was confirmed by the findings that insufficient lysosomal replenishment and damaged lysosomal clearance coincided with TFEB inactivation, which was mediated by mTOR hyperactivation in the renal tubular epithelial cells (TECs) of diabetic nephropathy. Furthermore, either TFEB overexpression or pharmacological activation of TFEB enhanced lysosomal clearance via promoting lysosomal biogenesis and protected TECs by reducing apoptosis in vitro . In addition, pharmacological activation of TFEB attenuated renal tubule injury, apoptosis, and inflammation in db/db mice. In conclusion, diabetes-induced mTOR activation represses TFEB function, thereby perturbing lysosomal homeostasis through impairing lysosomal biogenesis and clearance in TECs. Moreover, TFEB activation protects TECs from diabetic injuries via restoring lysosomal homeostasis.